Exploring circular economy imaginaries in European cities: A research agenda for the governance of urban sustainability transitions - Fratini, Chiara Farné; Georg, Susse; Jørgensen, Michael Søgaard (Journal of cleaner production, 2019)
This paper builds on the following research questions: 1) How is circular economy imagined in the academic literature in support of sustainability transitions in European cities? 2) How do European cities imagine circular economy as a knowable object of governance? 3) How can the circular economy imaginary be an opportunity for socially inclusive and environmentally desirable urban transitions? We engaged in a three-fold research endeavour to address these questions. Firstly, we conducted an in-depth literature review, mapping the emergence and developments of the circular economy concept in time and space with a specific focus on urban studies. Secondly, we analysed documented translations of the circular economy imaginary in three European metropolitan cities (Amsterdam, Paris and London) to explore the discourses, institutions, representations and social identities underpinning their respective translations, and reflect on how they diverge from each other and how they have the potential to deliver sustainable outcomes. Thirdly, these results were used to outline a research agenda that explores the relationship between the political and the epistemic domain of existing urban translations of circular economy across scales and places, to support future empirical investigations of whether and how circular economy imaginaries can support transformative pathways for socially inclusive and environmentally desirable value creation in cities. In so doing, this paper fosters reflexivity for both theory and practice in order to better understand how theorisations and the application of circular economy could be advanced in support of urban sustainability transitions.